Happiness and its predictors among undergraduate students in Malaysia: a systematic review - Yong, Claudia; Zainudin, Zaida Nor; Mohd Anuar, Mohd Ashraff; Wan Othman, Wan Norhayati (Human Resource Management Academic Research Society, 2022)
Happiness of university students gradually decreases throughout their studies and does not return to pre-university levels, which prompts the investigation of mental health and well-being in university students. The primary objectives of this systematic review includes to explore the predictors of happiness among undergraduate students in Malaysian universities, to outline the strategies and recommendations to foster happiness at the same time to explore future directions of happiness research in Malaysia. Using PRISMA guidelines, a systematic search of major databases including PubMed, MEDLINE, CINAHL, SCOPUS, and Google Scholar published in the English language between the year January 2013 to January 2022. A total of 11 articles were retrieved and their results were synthesized. The review found predictors such as religious commitment, Islamic-based gratitude strategy, creativity, sedentary behaviour, physical activity, trait emotional intelligence, extraversion personality, creativity, non-attachment, psychological well-being attributes, and youth engagement in meaningful activities to have positive relationship with happiness. Importantly, mediation effects were also examined in six studies indicating that consideration for effect modifiers should be performed following each predictors of happiness. In short, evidence showed there are specific traits, behaviours, strategies, and other domains of life that consistently predicts level of happiness. However, this review could not provide firm conclusions due to several reasons. Firstly, most of the studies were cross sectional studies with pre-determined predictors. Also, the factions of participants from selected Malaysian universities and the variation of predictors discussed prompts for further exploration in increased inclusivity and volume of participants as well as investigation with different methodologies.